A novel TLR7 agonist reverses NK cell anergy and cures RMA-S lymphoma-bearing mice. (2nd July 2016) - Wiedemann, Gabriela Maria; Jacobi, Severin Johannes; Chaloupka, Michael; Krächan, Angelina; Hamm, Svetlana; Strobl, Stefan; Baumgartner, Roland; Rothenfusser, Simon; Duewell, Peter; Endres, Stefan; Kobold, Sebastian
ABSTRACT: Toll-like receptor 7 (TLR7) agonists are potent immune stimulants able to overcome cancer-associated immune suppression. Due to dose-limiting systemic toxicities, only the topically applied TLR7 agonist (imiquimod) has been approved for therapy of skin tumors. There is a need for TLR7-activating compounds with equivalent efficacy but less toxicity. SC1, a novel small molecule agonist for TLR7, is a potent type-1 interferon inducer, comparable to the reference TLR7 agonist resiquimod, yet with lower induction of proinflammatory cytokines. In vivo, SC1 activates NK cells in a TLR7-dependent manner. Mice bearing the NK cell-sensitive lymphoma RMA-S are cured by repeated s. c. administrations of SC1 as efficiently as by the administration of resiquimod. No relevant toxicities were observed. Mechanistically, SC1 reverses NK cell anergy and restores NK cell-mediated tumor cell killing in an IFN-α-dependent manner. TLR7 targeting by SC1-based compounds may form an attractive strategy to activate NK cell responses for cancer therapy.